TANGGUNG JAWAB WALI TERHADAP PENJUALAN HARTA WARISAN ANAK YANG BERADA DI BAWAH PERWALIAN (STUDI KASUS PENGADILAN NEGERI DENPASAR NOMOR 691/PDT.P/2020/PN DPS) - Dewa Ayu Cahyani Paramitha; I Nyoman Putu Budiartha; Anak Agung Sagung Laksmi Dewi (Fakultas Hukum Universitas Warmadewa, 2024)
Marriage is a contract that allows men and women to work together in accordance with their natural inclinations and creates a reciprocal relationship between rights and obligations. Based on this background, the criteria for selecting guardians for minors who are not subject to parental authority and the responsibility of guardians for the sale of the inheritance of children under their supervision are articulated as problems. This research uses normative legal research methodology. Normative legal research is the study of secondary sources of information in the field of law. that the state has defended the rights of children, especially with regard to inheritance. If one of the parents of a child dies when the child is still an adult, the child automatically takes on the role of guardian, including the authority to sell movable and immovable property belonging to the child with due regard to the law. Because the child is cared for by his or her own parents, the child's rights are protected and their future is secured because the longest living parent is still present and responsible.